Integrating STEM based Education for Sustainable Development (ESD) to Promote Quality Education: A Systematic Literature Review - Irfan Fathurohman; Muhammad Fahriza Amri; Arifin Septiyanto; Riandi (Jurnal Penelitian Pendidikan IPA, 2023)
Promoting quality education through the integration of STEM-based Education for Sustainable Development (ESD) has become a significant area of interest. Integrating STEM-based ESD can enhance the quality of education by providing interdisciplinary learning opportunities that engage students in authentic, hands-on experiences. The objective of this study is to analyze existing empirical research on the utilization of STEM-ESD in order to investigate their effectiveness in fostering quality of education. The review process involved a systematic examination of journal papers published between 2018 and 2023, using both keyword search and snowballing techniques on the Scopus database. A total of 15 journal papers were selected for inclusion in this comprehensive review. The analysis indicates that STEM-ESD program is capable in increasing student self-efficacy and student engagement, STEM-ESD learning support student’s critical thinking skills and system thinking, Implementing Local Wisdom Based ESD can increase student knowledge, STEM learning in Sustainable Food Program as an effort to increase sustainable literacy in student, ESD can increase student’s environmental awareness. In this research there are a few implications such as that STEM-ESD need to be implemented in school curriculum in order to support education that is environmentally insightful.